Gender-based factors associated with hepatitis C testing in people who inject drugs: results from the French COSINUS cohort - Maria Patrizia Carrieri; Marc Auriacombe; Perrine Roux; Laélia Briand Madrid; Sébastien Kirchherr; Charlotte Kervran; Carole Chauvin; Marie Gutowski; Cécile Denis; Laurence Lalanne; Marie Jauffret-Roustide; Gilles Bertoia; et al. (BMJ Open)
Objective We identified factors associated with hepatitis C virus (HCV) testing in the previous 6 months in people who inject drugs (PWID) according to gender.Design COSINUS (Cohorte pour l’évaluation des facteurs Structurels et Individuels de l’USage de drogues) is a multisite longitudinal cohort study conducted between June 2016 and May 2019.Setting Harm reduction facilities in two French cities (Marseille and Bordeaux).Participants Eligibility criteria were as follows: 18 years of age or older, French speaking, regular use of illegal drugs or of prescribed medication, having injected at least once in the previous month and being able to provide informed consent to participate. We selected data for 298 participants (624 observations).Primary outcome Self-reporting HCV testing in the previous 6 months. Gender was defined as self-identifying as a woman, man or transgender person.Results Seventy-nine per cent (n=235) of the sample were men, and 63% (n=189) reported HCV testing in the previous 6 months. Our results suggest that men recently incarcerated (OR (95% CI): 3.26 (1.31, 8.12), p=0.011), those regularly attending harm reduction facilities (OR (95% CI): 2.49 (1.47, 4.22), p=0.001), and those with lifetime attempted suicide (OR (95% CI): 2.07 (1.08, 3.95), p=0.028) were more likely to have been tested for HCV in the previous 6 months, whereas older men were less likely (OR (95% CI): 0.46 (0.24, 0.89), p=0.022). Women who had slept in the street (OR (95% CI): 3.95 (1.12, 13.89), p=0.032) were more likely to have been tested for HCV in the previous 6 months, whereas those employed (OR (95% CI): 0.31 (0.12, 0.83), p=0.019) and those with lifetime attempted suicide (OR (95% CI): 0.39 (0.16, 0.97), p=0.044) were less likely.Conclusion Our results highlight the importance of improving current harm reduction facilities for PWID by adapting them to women’s needs and paying special attention to women’s mental health. Furthermore, in the context of primary care, improving provider training and reducing injection-related stigma may improve HCV testing uptake in older men and employed women.